Influencia del contexto Sociocultural en el placer sexual, de cuatro mujeres de edad adulta temprana, de El Dovio, Valle. (2021)
The present research work consists of understanding and identifying the influence of the sociocultural context: beliefs, taboos and prohibitions on the sexual pleasure of women, taking into account the influence of sexual education received from their environment, religion and the cultural context where the project is carried out, the municipality of El Dovio, Valle The research provides information on four (04) women with an age range between twenty (20) and forty (40) years of age, who participate voluntarily, based mainly on the analysis of beliefs, taboos and prohibitions, as influential in the decision-making about sexual behaviors. The study has a qualitative, phenomenological methodology, developed through semi-structured interviews, a focus group and a projective activity called body mapping, likewise, the interpretation of the data or information obtained is carried out, through the content analysis technique. Consequently, the following results are obtained: it shows as the main axes of influence on women's sexual pleasure, the family as a direct and primary environment, the culture framed by patriarchy and that, within itself, carries a historical reality and the statement of the hypothesis that there is a correlation between personality and sexual desire.